Diffusion and phase relaxations within the interphase domain of polymer blendlike particles - Pekcan, Önder (Wiley, 1996)
A single-photon counting technique in conjunction with a direct energy transfer (DET) method was used to study the diffusion of small dye molecules within the interphase domain of anthracene (An)- and/or phenanthrane (Phe)-labeled poly(methyl methacrylate) (PMMA) particles sterically stabilized by polyisobutylene (PIB). Mean lifetimes of fluorescing donor molecules were measured during diffusion. A Fickian model for diffusion was employed to fit the experimental data and diffusion coefficients were found to be around 10 -19 and 10 -16 cm 2 /s at room and above glass transition temperatures (T g ) for the corresponding samples, respectively. A reversed Gaussian distribution was detected for the PMMA phase density at the interphase domain. An increased amount of self-quenching of naphthalene (N) dyes labeled to the PMMA phase was investigated against annealing temperature above T g and the results were attributed to phase relaxations at the interphase domain.